Optical solitons of the complex Ginzburg–Landau equation having dual power nonlinear form using ?6-model expansion approach - Isah, Muhammad Abubakar; Yokus, Asif (Mehmet Yavuz, 2023)
This paper employs a novel ?6-model expansion approach to get dark, bright, periodic, dark-bright, and singular soliton solutions to the complex Ginzburg-Landau equation with dual power-law non-linearity. The dual-power law found in photovoltaic materials is used to explain nonlinearity in the refractive index. The results of this paper may assist in comprehending some of the physical effects of various nonlinear physics models. For example, the hyperbolic sine arises in the calculation of the Roche limit and the gravitational potential of a cylinder, the hyperbolic tangent arises in the calculation of the magnetic moment and the rapidity of special relativity, and the hyperbolic cotangent arises in the Langevin function for magnetic polarization. Frequency values, one of the soliton’s internal dynamics, are used to examine the behavior of the traveling wave. Finally, some of the obtained solitons’ three-, two-dimensional, and contour graphs are plotted. © 2023 by the authors.
Keywords: complex Ginzburg–Landau equation; dual power-law nonlinearity; soliton solutions; ?6-model expansion method